Voltage-gated potassium channelopathy: an expanding spectrum of clinical phenotypes. (10th January 2013) - Shribman, Sam; Patani, Rickie; Deeb, Jacquie; Chaudhuri, Abhijit
Abstract : Autoimmune voltage-gated potassium channelopathies represent a wide and expanding spectrum of neurological conditions. We present a case demonstrating the phenotypic heterogeneity of antivoltage-gated potassium channels (VGKC)-associated disorders. Such cases may easily be dismissed as functional disorders at first presentation. We propose that there must remain a high index of suspicion for antiVGKC-associated disorders in cases where there are transient neurological disturbances in atypical spatial and temporal distributions.